A will to write - Barnett, Ron; Leibowitz, Brenda (South African Journal of Higher Education, 2016)
This article is based on an interview conducted by Brenda Leibowitz with Ron Barnett, noted author of over 20 academic books and 100 articles, at the 2012 annual Higher Education Teaching and Learning Association of Southern Africa (HELTASA). The interview deals with topics including: the challenge of formulating and articulating a definite thesis, the importance of polishing and crafting drafts, keeping multiple audiences in mind, the different demands of writing articles and books, the value of poetry and fiction, how to keep going as a writer, issues of identity, and maintaining a will to write. The article continues with a set of joint critical reflections on the nature of academic writing and concludes with the suggestion that writing can enhance academics’ understanding of themselves.